2018
DOI: 10.2340/16501977-2298
|View full text |Cite
|
Sign up to set email alerts
|

Bladder irrigation with Chlorhexidine reduces bacteriuria in persons with spinal cord injury

Abstract: Bladder irrigation with chlorhexidine, using intermittent self-catheterization, reduced bacteriuria in the majority of subjects with spinal cord injury and bacteriuria. The addition of bladder irrigation was practically feasible in the short time-frame of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…The urine samples were taken for the first urine culture three hours after irrigation. The results showed that irrigating the bladder with chlorhexidine alternately decreased bacteriuria in the majority of the patients with spinal cord injury (39).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The urine samples were taken for the first urine culture three hours after irrigation. The results showed that irrigating the bladder with chlorhexidine alternately decreased bacteriuria in the majority of the patients with spinal cord injury (39).…”
Section: Discussionmentioning
confidence: 96%
“…The findings showed that preventing the colonization of hospitalized patients in ICUs with chlorhexidine baths once a day along with mupirocin could be a potential preventive strategy for male patients, as it significantly decreased candiduria and bacteriuria (38). Also, Wikstrom et al (39) aimed to assess the effect of bladder irrigation with chlorhexidine on reducing the incidence of bacteriuria in patients with spinal cord injury. They investigated 50 patients from two populations of hospitalized patients and patients living at home by random sampling from four rehabilitation centers in Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…Other interventions have been proposed for minimizing both extraluminal and intraluminal colonization pathways with conflicting reports and guidance for effectiveness in preventing CAUTI. e effectiveness of antimicrobial irrigation of the bladder followed by drainage had been contested in CDC guidelines [20] but more recently reported effective elsewhere [21,22]. Effectiveness of antimicrobial catheter coatings has similarly been reported to be inconclusive [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Within this pilot study, it could be demonstrated that intravesical instillations with oxybutynin hydrochloride did not affect routine tests for a total of 25 model substances, and the method of bladder instillation as such does not appear to require specific attention in the context of doping control procedures. However, future studies should clarify whether this also applies to bladder irrigation procedures with antiseptics such as chlorhexidine …”
Section: Discussionmentioning
confidence: 99%
“…However, future studies should clarify whether this also applies to bladder irrigation procedures with antiseptics such as chlorhexidine. 14…”
Section: Discussionmentioning
confidence: 99%